STUDY OF PHENOTYPIC CHARACTERS VARIABILITY OF THE SILKMOTH COCOON FROM THE NATIVE GENETIC STOCK OF BOMBYX MORI L. SP. - ALEXANDRA MATEI; MAGDA ANDRONE; C. UNGUREANU (Scientific Papers Animal Science and Biotechnologies, 2023)
This study had aims the analysis of phenotypic characters variability of silkmoth cocoon within the native genetic stock of Bombyx mori L. sp. The biological material was represented by 72 races consisting of the gene stock of Bombyx mori sp., grouped by their origin. The main phenotypical ad quantitative parameters of the races that represent the gene stock of Bombyx mori sp., present the following values: raw cocoon weight (1.445-2.361 g), cocoon shell weight (0.240-0.520 g), fiber length (746-1356 m), metric number of fiber (2917-3764 m/g). Depending on the quantitative parameters value, the silkworm races are being used differently, entire genetic stock being destined for various technological levels, as follows: 4 active races (parents of hybrids), 4 candidate races for parents of hybrids, 64 races in preservation.